Genetic and morphological characterization of United States tea (Camellia sinensis): insights into crop history, breeding strategies, and regional adaptability - Clarke, Caitlin; Richter, Brantlee Spakes; Rathinasabapathi, Bala (Frontiers in Plant Science, 2023)
Multiple introductions of tea (Camellia sinensis) to the United States since the 1850s have resulted in US tea germplasm that are currently poorly characterized. To resolve questions concerning the provenance and regional adaptability of US tea germplasm, 32 domestic individuals were evaluated using 10 InDel markers, and compared with a background population of 30 named and registered Chinese varieties of tea. The marker data were analyzed via a neighbor-joining cladistic tree derived from Nei’s genetic distance, STRUCTURE, and Discriminant Analysis of Principal Components, which revealed four genetic groups. Nineteen individuals selected from the four groups were further assessed for seven leaf traits, two floral descriptors, and leaf yield, to identify plants best adapted to Florida field conditions. Our analyses compared with available historical records led us to estimate the most likely provenance of some of the US individuals, to precisely identify tea plant material and to choose most diverse accessions for breeding tea improved for adaptability, yield and quality.